Representação política de mulheres na Câmara Federal: processo representativo, instituições e populismo de direita - Castro, Leonardo Aires de (2022)
Using the theoretical perspective of Feminist Institutionalism, in which institutions are structured in masculine values that creates barriers for women political representation, we aimed to study women representation in the Brazilian Federal Chamber from 2003 to 2019, analyzing political representation as an institutional process that responds to numerous incentives. We ask if the women’s presence in this institution implicates the descriptive representation and if the electoral victory of populist governments impacts the legislative production on gender issues. Our argument articulates that women’s representation is not linear, so their presence in the political arena does not necessarily translate into substantive politics and, in circumstances of right-wing populist leaders and values rises, gender agendas may be captured. Throughout the thesis we built a theoretical overview and used a mixed methodology to investigate the process of women representation in Brazil and the impact of populist governments on gender issues agenda, using comparative research between Brazil and the United States of America. We indicate that women representation in Brazil finds it difficult to be carried out at the hands of elected deputies because of institutional obstacles, given the low number of women in this arena and the structures that prevent and constrain the effectiveness of their actions. On the other hand, right-wing populist governments had a positive impact on the number of women elected, but not necessarily on the production of gender issues agenda by parliament, depending on the institutional arrangement, since in Brazil there was a negative impact and in the United States a positive impact.